PENGARUH BELANJA OPERASIONAL DAN BELANJA MODAL TERHADAP EKUITAS DANA (SURVEI PADA SKPD KABUPATEN SIGI) - Imelda, Imelda (Katalogis, 2017)
The purposes of this study are: 1) to determine the growth of operational expenditure, capital expenditure, and funds equity on govermental working units in Sigi; 2) to determine and analyze simultaneous influence of operational expenditure and capital expenditure of fund’s equity on govermental working units in Sigi; 3) to determine and analyze the influence of operational expenditure on fund’s equity; 4) to determine and analyze the influence of capital expenditure on funds equity in govemental working units of Sigi. The results shows that the R2 value of 0,968 or 96,8% means that operational expenditure and capital expenditure have influence on fund’s equity of 96,8% in govermental working units of Sigi. While 3,2% influenced by variable that are not studied.